2006
DOI: 10.1016/j.jcf.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Fecal elastase-1: Utility in pancreatic function in cystic fibrosis

Abstract: Early detection and management of pancreatic insufficiency is essential to optimize health and outcomes in cystic fibrosis patients. The gold standard measures for assessment of pancreatic function are direct pancreatic stimulation tests, which have numerous limitations. Estimation of fecal elastase-1 level to determine pancreatic function is an attractive alternative as the test is simple, rapid, cost-effective and easy to perform even in children. This review summarizes the data from studies reflecting the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 37 publications
1
23
0
6
Order By: Relevance
“…Many investigators have confirmed the theoretical advantage of "elastase 1" by showing low variability and stability under storage at room temperature. 8,10,29 Our study confirmed the longterm (>300 days) reproducibility of the fecal pancreatic elastase test. In cases of severe exocrine insufficiency, patients who initially showed fecal pancreatic elastase levels of <200 µg/g also exhibited abnormal values in the second test (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Many investigators have confirmed the theoretical advantage of "elastase 1" by showing low variability and stability under storage at room temperature. 8,10,29 Our study confirmed the longterm (>300 days) reproducibility of the fecal pancreatic elastase test. In cases of severe exocrine insufficiency, patients who initially showed fecal pancreatic elastase levels of <200 µg/g also exhibited abnormal values in the second test (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Fecal pancreatic elastase measurement is a clinically valuable alternative to a direct function test, because it is harmless for infants and can detect pancreatic insufficiency with reasonable sensitivity and specificity. 29 This test is suitable for longitudinal follow-up of exocrine function in pancreatic sufficient patients and for deciding the timing of enzyme replacement. 32,33 In conclusion, compared with other indirect tests, fecal pancreatic elastase is a sensitive and specific test of exocrine pancreatic function, though it never attains the sensitivity and specificity of the direct function test.…”
Section: Discussionmentioning
confidence: 99%
“…FE-1 is well documented in quantitative studies to be stable during intestinal transit and studies demonstrate significant correlation between fecal elastase and levels of other pancreatic enzymes such as duodenal lipase, amylase, trypsin, and bicarbonate concentration [2][3][4][5][6]. Fecal elastase is concentrated in human feces compared with pancreatic juice and is a simple, non-invasive and inexpensive test [2,7,8].…”
mentioning
confidence: 99%
“…vitamin K ad- ministration. If the diagnosis of CF is confirmed by sweat chloride analysis, pancreatic insufficiency should be confirmed with fecal elastase analysis, as this is both a sensitive and specific marker of pancreatic exocrine function (13).…”
Section: Discussionmentioning
confidence: 99%